2019
DOI: 10.9734/cjast/2019/v37i630333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Type Mulch on Growth, Yield Attributes and Yield of Brinjal (Solanum melogena)

Abstract: Field experiment was conducted at Krishi Vigyan Kendra, Aurangabad and at farmer’s field during 2012 and 2013 to Effect of different type mulch on growth, yield attributes and yield of Brinjal (Solanum melogena). The experiment was conducted in randomized block design with three treatments viz; Black polyethylene mulch, Wheat straw mulch and no mulch (control). The result reveled that maximum plant height 78.0 cm, maximum no. of leaves per plant 366.8 and maximum number of shoots per plant 32.60 were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
3
1
0
Order By: Relevance
“…The results revealed that, these crop growth and yield attributes are significantly higher in the drip with plastic mulch (A) as compared to the rest of the treatments. These results are in agreement with the results in references [8,11].…”
Section: Soil Temperaturesupporting
confidence: 93%
See 3 more Smart Citations
“…The results revealed that, these crop growth and yield attributes are significantly higher in the drip with plastic mulch (A) as compared to the rest of the treatments. These results are in agreement with the results in references [8,11].…”
Section: Soil Temperaturesupporting
confidence: 93%
“…During harvesting the leaves are maximum observed in black plastic mulch (A) and the least in Control (K). These results are in line with agreement with the results of [8,11].…”
Section: Number Of Leavessupporting
confidence: 93%
See 2 more Smart Citations